The Relationship Between the Expression of CRBN in Peripheral Blood and the Severity and Prognosis of Adult Sepsis - Kuang Z; Gu Q (International Journal of General Medicine, 2023)
Zhiming Kuang,1 Qiuping Gu1,2 1Department of Critical Care Medicine, Ganzhou People’s Hospital, Ganzhou, Jiangxi Province, 341000, People’s Republic of China; 2Department of Gastroenterology, Ganzhou People’s Hospital, Ganzhou, Jiangxi Province, 341000, People’s Republic of ChinaCorrespondence: Qiuping Gu, Department of Gastroenterology, Ganzhou People’s Hospital, No. 16, Meiguan Avenue, Zhanggong District, Ganzhou City, Jiangxi Province, People’s Republic of China, Tel +86-18214932018, Email zhangdi2@mail.sdufe.edu.cnObjective: To investigate the correlation between the expression of cereblon (CRBN) protein in peripheral blood and the severity and prognosis of sepsis.Methods: A total of 130 patients with sepsis admitted to our hospital were selected as the observation subjects (sepsis group). The patients were divided into mild group, moderate group and severe group according to their conditions. The patients were divided into survival group and death group according to their living conditions within 28 days after admission. 130 health individuals were selected as the control group. The levels of CRBN mRNA, CRP and PCT in peripheral blood were detected.Results: The levels of serum CRBN mRNA, CRP, and PCT in patients with sepsis were higher than those in the control group (P< 0.05); As the condition worsens, the levels of CRBN mRNA, CRP, and PCT gradually increase, and there are statistically significant differences among patients with mild, moderate, and severe sepsis; Correlation analysis showed that the expression of CRBN mRNA in sepsis patients was positively correlated with CRP, PCT levels, APACHE II score and SOFA score (P< 0.05); the 28-day cumulative survival rate of patients with high CRBN mRNA expression was significantly lower than that of patients with low CRBN mRNA expression (P< 0.05); compared with the survival group, the levels of serum CRBN mRNA, CRP and PCT in the death group were significantly higher (P< 0.05); the AUC of death in sepsis patients diagnosed by CRBN mRNA, CRP and PCT was 0.961, the combined diagnostic efficacy was higher than that of single detection (P< 0.05).Conclusion: The expression level of CRBN in the peripheral blood of patients with sepsis is increased, which is related to the severity and prognosis of the patients. The combination of CRP and PCT has certain diagnostic value for the death of sepsis patients.Keywords: sepsis, cereblon protein, prognosis, severity